Internal control and audit in the public sector: The need to synchronize occupational standards in the digital economy - Natal'ya E. SPIRIDONOVA (International Accounting, 2026)
Subject. This article analyzes the content of occupational standards in the field of internal control and internal auditing, which set qualification requirements for specialists and provide guidelines for developing educational programmes. Objectives. The article aims to systematize the requirements for the qualifications and digital skills of specialists performing control functions within an economic entity, identify areas of concern in the current system distinguishing the profession lines of Internal Controller and Internal Auditor, and also develop proposals for improving and harmonizing the occupational standards under consideration. Methods. For the study, I used analysis and synthesis, grouping, comparison, generalization, and specification. Results. Based on a critical analysis of the occupational standards – Compliance Officer (Internal Controller) and Internal Auditor, the article systematizes points that show the impact of digitalization on control activities, explains the imbalance between the requirements for the qualification level, education, and digital literacy of internal control specialists, and it identifies contradictions caused by the regulatory separation of internal control and internal audit. The article presents formulated suggestions for addressing identified shortcomings and improving the system of qualification requirements for specialists carrying out control functions. Conclusions. The conducted study confirms the need to further think about the distinction between control and audit functions in practice, as well as address the imbalance between the requirements for the qualifications, education, and digital literacy of internal control specialists.